Multiplying out the brackets gives:
20 = -4v + 8v + 56
Simplifying by adding the like terms 8v and -4v:
20 = 4v + 56
Subtracting 56 from both sides:
-36 = 4v
Dividing both sides by 4:
v = -9
Therefore, the solution to the equation is v = -9.
20=-4v+8(v+7)
7 answers
-4y+28=6(y-7)
Expanding the brackets gives:
-4y + 28 = 6y - 42
Simplifying by adding 4y to both sides:
28 = 10y - 42
Adding 42 to both sides:
70 = 10y
Dividing both sides by 10:
y = 7
Therefore, the solution to the equation is y = 7.
-4y + 28 = 6y - 42
Simplifying by adding 4y to both sides:
28 = 10y - 42
Adding 42 to both sides:
70 = 10y
Dividing both sides by 10:
y = 7
Therefore, the solution to the equation is y = 7.
Solve for .
Simplify your answer as much as possible.
-4(u-7)=4u-4
Simplify your answer as much as possible.
-4(u-7)=4u-4
Expanding the brackets gives:
-4u + 28 = 4u - 4
Simplifying by adding 4u to both sides:
28 = 8u - 4
Adding 4 to both sides:
32 = 8u
Dividing both sides by 8:
u = 4
Therefore, the solution to the equation is u = 4.
-4u + 28 = 4u - 4
Simplifying by adding 4u to both sides:
28 = 8u - 4
Adding 4 to both sides:
32 = 8u
Dividing both sides by 8:
u = 4
Therefore, the solution to the equation is u = 4.
8w-19=5(w-8)
Expanding the brackets gives:
8w - 19 = 5w - 40
Simplifying by subtracting 5w from both sides:
3w - 19 = -40
Adding 19 to both sides:
3w = -21
Dividing both sides by 3:
w = -7
Therefore, the solution to the equation is w = -7.
8w - 19 = 5w - 40
Simplifying by subtracting 5w from both sides:
3w - 19 = -40
Adding 19 to both sides:
3w = -21
Dividing both sides by 3:
w = -7
Therefore, the solution to the equation is w = -7.